Correction: Bimetallic oxyhydroxide in situ derived from an Fe2Co-MOF for efficient electrocatalytic oxygen evolution. Issue 25 (21st June 2021) - Ling, Xintong; Du, Feng; Zhang, Yintong; Shen, Yan; Gao, Wa; Zhou, Bo; Wang, Zhiyuan; Li, Guoling; Li, Tao; Shen, Qing; Xiong, Yujie; Wang, Xiaoyong; et al.
Abstract : Correction for 'Bimetallic oxyhydroxide in situ derived from an Fe2 Co-MOF for efficient electrocatalytic oxygen evolution' by Xintong Ling et al., J. Mater. Chem. A, 2021, 9, 13271–13278, DOI: ; 10.1039/D1TA02159A .